2010
DOI: 10.13181/mji.v19i3.403
|View full text |Cite
|
Sign up to set email alerts
|

The association of plasminogen activator inhibitor-1 level with ischemic stroke (preliminary study)

Abstract: AbstrakTujuan Kadar plasminogen activator inhibitor-1 Hasil Kadar PAI-1 yang tinggi ditemukan lebih sering pada penderita stroke iskemik daripada subjek kontrol (21.1% vs. 7.9 % dengan OR 3.1;. Analisa terhadap semua subjek yang diteliti menunjukkan adanya hubungan negatif yang lemah namun bermakna antara kadar PAI-1 dengan usia (r = -0.4; P = 0.000). Kadar PAI-1 yang tinggi ditemukan lebih sering pada subjek berusia muda (40 -58 tahun) daripada subjek berusia lebih tua ( 60 -84 tahun) (20 vs. 9 .8 %) (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…16 In one case control study design, it was concluded that, high PAI-1 level was found more frequent in ischemic stroke subjects. 17 Together with the recent observation that the activators of PPARγ a ligand reduces the incidence of stroke in patients with type 2 diabetes, this review supports the concept that rosiglitazone is effective drug against ischemic injury. 18 Of the two FDA-approved thiazolidinediones, pioglitazone is known to cross BBB more efficiently than rosiglitazone, but the affinity of pioglitazone to PPAR is 10 times lower (Kd of 400 nM) than for rosiglitazone (Kd of 40 nM).…”
Section: Rosiglitazone -Neuroprotective Effects In Brain Ischaemia (Ssupporting
confidence: 61%
“…16 In one case control study design, it was concluded that, high PAI-1 level was found more frequent in ischemic stroke subjects. 17 Together with the recent observation that the activators of PPARγ a ligand reduces the incidence of stroke in patients with type 2 diabetes, this review supports the concept that rosiglitazone is effective drug against ischemic injury. 18 Of the two FDA-approved thiazolidinediones, pioglitazone is known to cross BBB more efficiently than rosiglitazone, but the affinity of pioglitazone to PPAR is 10 times lower (Kd of 400 nM) than for rosiglitazone (Kd of 40 nM).…”
Section: Rosiglitazone -Neuroprotective Effects In Brain Ischaemia (Ssupporting
confidence: 61%
“…The link between PAI-1 and ischaemic stroke has been well studied [35]. Elevated levels of PAI-1 not only positively correlated with the severity of stroke but also greatly increased the failure rate of thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the plasma concentration of PAI-1 with increasing age has been described. 10 Therefore, we suspect that the association between levels of PAI-I and the profile “HIV-negative stroke” is due to a residual confounding effect of age.…”
Section: Discussionmentioning
confidence: 99%